Biochemical characterization of the thrombin inhibitor of the tick, Ornithodoros savignyi, and investigation into the expression of its recombinant forms - Gaspar, A.R.M. (Anabella Regina Marques) (University of Pretoria, 2013)
Dissertation (MSc (Biochemistry))--University of Pretoria, 2007.